Suicide related to the COVID‑19 pandemic in India: A systematic review - Al‑Mamun, Firoj; Kaggwa, Mark Mohan; Hosen, Ismail; Sikder, Md. Tajuddin; Griffiths, Mark D.; Mamun, Mohammed A. (Discover Psychology, 2023)
Background: The suicide rate has increased during the pandemic in India. Moreover, several studies, especially pressmedia reporting suicide studies have been conducted but no systematic review has been attempted in this context. Therefore, the present study systematically investigated the risk factors associated with suicidal behaviors, and the method of suicide during the COVID-19 pandemic in India. Methods: Following the PRISMA guidelines, a systematic search was performed to include papers published up until September 30, 2022. From an initial 144 papers, 18 studies which met the inclusion criteria were included in the present review. The Pierson’s method was used for quality assessment of the included studies in the present review. Results: The risk factors associated with suicide comprised: (i) socio-demographic factors (e.g., being aged between 31 and 50 years, male, married, unemployed), (ii) behavior and health-related factors (e.g., unavailability of alcohol and alcohol withdrawal symptoms, poor state of physical health and health issues, family disputes, relationship complexities, and sexual harassment), (iii) COVID-19-related factors (e.g., fear of COVID-19, COVID-19 test results, quarantine or isolation, financial hardship due to the pandemic, having influenza-like symptoms, experiencing stigmatization and ostracism despite testing negative, separation from family due to transport restrictions, misinterpreting other illness symptoms as COVID-19, saving the village from infection, watching COVID-19 videos on social media, online schooling, perceived stigma toward COVID-19, and being suspected of having COVID-19), and (iv) psychopathological stressors (depression, loneliness, stress, TikTok addiction, and poor mental health, suicidal tendencies, helplessness, and worrying). Hanging was the most common method of suicide. In addition, jumping from high buildings, poisoning, drowning, burning, cutting or slitting throat or wrists, self-immolation, medication overdose, electrocution, pesticide, and gun-shot were also used to carry out the suicide. Conclusions: Findings from this research suggest multiple reasons for suicide during the COVID-19 pandemic and knowledge of such factors could aid in developing suicide prevention strategies focusing the most vulnerable cohorts inside and outside India.
Keywords: COVID-19 suicide; Suicide; Suicidal behavior; Suicide risk factors; Suicide methods; Media reported suicide